Development Of IoT-Based Smart Control System Learning Media That Is Adaptive To Regulate Soil Moisture And Humidity In The Intelligent Control System Course - Setia Budi, Christian; Nyoman Santiyadnya; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2024)
This study aims to create learning media used in the Undiksha Electrical Engineering Education Study Program, especially in the intelligent control system course aimed at supporting the learning process. This research is included in the type of research and development (R&D) research. This study uses quantitative descriptive analysis techniques to process data from content experts, media experts, large groups and small groups. The results of the study obtained: The results of the content expert test got a percentage of 95.5% while the results of the media expert test got a percentage of 96.1%, including in the very feasible qualification. The results of the small group test got a percentage of 100%, with the lowest respondent results at R1 with a score of 38. The results of the large group test got a percentage of 100%, with the lowest respondent results at A13 with a score of 36. Based on the results of the study, the Adaptive IoT-Based Smart Control System to Regulate Air Temperature and Soil Moisture is feasible to be used for learning media in the Intelligent Control System Course of the Undiksha Electrical Engineering Education Study Program.